Distribution and status of the Rufous-tailed Jacamar Galbula ruficauda (Aves: Galbulidae) in Paraguay - Centrón, Silvia (2016)
Rufous-tailed Jacamar Galbula ruficauda is known from few records in Paraguay, all during the last 20 years. The species has been recorded in the northern Chaco and Paraguayan Pantanal, with all confirmed records from Alto Paraguay department. Here we summarise all reports and localities of the species in Paraguay to date. The species is categorized as Data Deficient at the national level, but may be more widely distributed than is currently recognised.